Impact of dental caries on the daily lives of geriatric patients visiting dental hospitals in Rawalpindi, Pakistan - Saadia Ayub; Saman Waqar; Muhammad Tahir Muneeb (Tabriz University of Medical Sciences, 2024)
Background. The objectives were to assess the impact of dental caries on the daily living of the geriatric population and determine the factors that influence the relationship between dental health and the daily living of the geriatric population. Methods. A descriptive cross-sectional study was carried out over six months at Rawalpindi's public and private dental hospitals. Participants aged≥60 years, both male and female, were selected. The calculated sample size was 281. Desired sample from one of the dental hospitals was collected using a non-probability consecutive sampling strategy. Data about sociodemographic characteristics and the DMFT index were collected. Adapted validated tool dental impact on daily living (DIDL) was used to assess the impact of dental health on daily living. Results. Chi-squared test of association showed a positive association between the DIDL and sociodemographic variables, including age (P=0.001), gender (P=0.001), education (P=0.001), income (P=0.001), occupation (P=0.029), marital status (P=0.001), living arrangement (P=0.001), and history of chronic illnesses (P=0.001). The association between the DMFT index and DIDL also showed statistically significant results (P=0.001). Binary logistic regression analysis indicated that gender (OR=6.98, P=0.005) and the individual's dental health (OR=6.43, P=0.001) were the strongest predictors of the impact experienced in daily life activities. The overall model was statistically significant (χ2=51.24, P=0.001), and the variables were responsible for 32.4% of the variance in the outcome variable. Conclusion. The study provides strong evidence that sociodemographic factors, DMFT index, gender, and individual dental health significantly contribute to the impact of dental health on daily living. Gender and individual dental health emerge as particularly influential predictors. These findings emphasize the need for targeted interventions and awareness programs, especially for groups with a higher risk of experiencing a significant impact on daily life due to dental issues.